THE BUILD OF CUSTOMER LOYALTY BY POLICY OF PRICE ON SALES PROMOTION - Taufik, Edi Rahmat (Management Science Research Journal, 2022)
The research project to determine the influence of price policy and sales promotion on customer loyalty at home industri Beef Wagyu on Serang City. The research method using direct observation by survey method and quantitative approach. The sample was done be taken by 66 respondent of customer beef wagyu. The technique analysis data using multiple regression analysis to explore the influence between variable independent and dependent variable. The result of this research is the price have a negative influence on customer loyalty, sales promosion have positive influence on customer loyalty, and then, there are an influence between a policy of price and sales promotion on customer loyalty. The implication of this research a customer loyalty can be explained by price and sales promotion